ANALISIS BIAYA KUALITAS (QUALITY COST) TERHADAP PENCAPAIAN LABA PADA RUMAH SAKIT SUMBER HIDUP KOTA AMBON - Dominggus B Jotlely; Steven Siaila (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
Quality costs are costs associated with preventing, identifying, repairing and correcting low quality products and with the opportunity costs of lost production and sales time as a result of poor quality. Quality costs are evaluated by comparing actual costs with budgeted costs. Comparison of quality costs still uses the absolute amount of costs actually spent with those budgeted.This study aims to calculate and analyze the costs of quality (prevention costs, valuation costs, failure costs) and profit achievement, so it can be seen that the variable costs have a significant relationship to the profit achievement of the Sumber Sumber Ambon Hospital. This type of research uses a quantitative methodology, by calculating the values in the financial statements of Sumber Hidup Hospital Ambon in 2015 - 2017.The results showed that the cost of quality has a positive and significant effect on the achievement of profits simultaneously. Partially, prevention costs have a positive and significant effect on the achievement of earnings, valuation costs have no significant effect on the achievement of profits, while the cost of failure has a negative and significant impact on the achievement of profits at the Ambon Sumber Hidup Hospital in 2015 - 2017. Keywords: Quality Cost, Achievement of Profit